A case of rhabdomyosarcoma of the right ventricle. Issue 12 (December 1978) - Firmin, R; Lowes, A; Hickson, B
Abstract : A patient is described who presented with symptoms suggesting pericarditis and cardiac tamponade, and who was found at necropsy to have a rhabdomyosarcoma of the right ventricle. The presenting features of right ventricular tumours are discussed and some useful pointers to the correct diagnosis suggested.